HDR Syndrome – A Follow-up Genotype-Phenotype Analysis of a de novo Missense Thr272Ile Mutation in Exon 4 of GATA3 - Gomes, T. S.; Gortner, L.; Dockter, G.; Leitner, D.; Thakker, R. V.; Rohrer, T. (Klinische Pädiatrie, 2012)
Hypoparathyroidism, sensorineural deafness and renal dysplasia (HDR) syndrome (MIM 146255) is a rare autosomal dominant disorder caused by mutations in the gene encoding GATA3, a dual zinc-finger transcription factor involved in vertebrate embryonic development. In this clinical case study we report on a follow-up of a phenotype associated with a GATA3 mutation. HDR syndrome was clinically diagnosed at age of 1.5 years in a boy with a de novo heterozygous missense (c.815C→T) mutation, Thr272Ile, in exon 4 of the GATA3 gene. Both parents were negative for Thr272Ile.At age of 17 months, the patient had a weight of 10.7, a body length of 78 cm, and a head circumference of 47.5 cm. By the age of 7 years, growth is age-appropriate, severe bilateral hearing loss (dB 60) was corrected by hearing aids. However, cognitive development (auditory sensory memory and language abilities) is at the lower ends of the test scores.In conclusion, a mildly impaired clinical course was achieved by the age of 7 years in a patient with HDR syndrome; this report adds to the body of data on genotype-phenotype analysis in HDR syndrome. ·
Keywords: HDR syndrome; GATA3; Thr272Ile; genotype; phenotype